Migration scenarios for gender apartheid and asylum: when International Criminal Law and International Refugee Law Meet - Lara-Zuzan Golesorkhi (Data & Policy)
A multi-year process of debate around draft articles for a Crimes Against Humanity Treaty is underway and calls to categorize gender-based persecution as a stand-alone crime and to codify gender apartheid form fundamental aspects of discussion. These developments in international criminal law are significant to anticipate forced migration as recent changes in asylum regulations across the EU suggest. Between December 2022 and February 2023, Sweden, Finland, and Denmark moved to grant asylum to women and girls from Afghanistan on general risks of gender-based persecution. This falls in line with the EU Agency for Asylum establishing that the accumulation of repressive measures against women and girls in the country, which have been described as gender apartheid, amounts to persecution. In efforts to offer new perspectives on foresight in forced migration, I use case study method and legal-institutional analysis to delineate migration scenarios for gender apartheid and asylum. On the example of Afghanistan, I compare Sweden, Finland, and Denmark as case studies in which asylum is granted to women and girls on general risks of gender-based persecution in contrast to Germany and France as case studies for main destination countries of Afghan asylum-seekers absent of such policies. I explore factors towards policy in/action and provide outlooks for further lines of inquiry regarding anticipatory methods in forced migration.